CD19-targeting CAR T-cell therapy in patients with diffuse systemic sclerosis: a case series - Auth, Janina; Müller, Fabian; Völkl, Simon; Bayerl, Nadine; Distler, Jörg H.W.; Tur, Carlo; Raimondo, Maria Gabriella; Chenguiti Fakhouri, Sara; Atzinger, Armin; Coppers, Birte; Eckstein, Markus; Liphardt, Anna-Maria; et al. (The Lancet Rheumatology, 2024)
Background: CD19-targeting chimeric antigen receptor (CAR) T-cell therapy has shown remarkable outcomes in patients with systemic lupus erythematosus. The effects of CD19-targeting CAR T cells on organ manifestations in patients with systemic sclerosis have yet to be characterised. B cells have a central role in the pathogenesis of systemic sclerosis. We present a detailed analysis of the effects of CD19-targeting CAR T-cell therapy in patients with systemic sclerosis. Methods: Six patients with severe diffuse systemic sclerosis with an insufficient response to at least two treatments were consecutively recruited at the Department of Internal Medicine 3, University Hospital Erlangen (Erlangen, Germany) to receive CD19-targeting CAR T-cell treatment (1 × 106 CAR T cells per kg bodyweight). Events were predefined by progression of interstitial lung disease, onset of congestive heart failure, onset of renal failure, onset of arterial hypertension, or initiation of new immunosuppressive or antifibrotic therapy. Event-free time or treatment intensification after study entry was the primary outcome. Key secondary outcomes included changes in the modified Rodnan Skin Score (mRSS), imaging (a component of the assessment of lung fibrosis), laboratory assessments, patient-reported outcomes, and a modified version of the American College of Rheumatology Composite Response Index in Systemic Sclerosis (ACR-CRISS), assessed at baseline, 3 months, 6 months, 9 months, and 12 months. Findings: Between April 20, 2022, and Nov 8, 2023, six patients with severe diffuse systemic sclerosis (median age 42 years [IQR 36–53]; four men and two women; all White European) were recruited and received CD19-targeted CAR T-cell therapy. The median follow-up time was 487 days (IQR 342–585). No events occurred within the observational period. Probability of improvement in the ACR-CRISS score increased to a median of 100% (IQR 100–100) at 6 months. Median mRSS decreased by 31% (IQR 29–38), corresponding to a median of 8 points (IQR 7–13) within 100 days. The extent of disease on CT scan decreased by a median of 4% (IQR 3–4) due to reduction of ground-glass opacities while the reticular pattern remained stable. Forced vital capacity improved by a median of 195 mL (IQR 18–275) at the latest observational timepoint. Interpretation: We provide the first evidence that CD19-targeting CAR T-cell therapy might intercept with the progression of fibrotic organ manifestations in patients with systemic sclerosis. Funding: Deutsche Forschungsgemeinschaft, Deutsche Krebshilfe, ELAN-Foundation Erlangen, IZKF Erlangen, and Bundesministerium für Bildung und Forschung.
CRIS-Team Scopus Importer:2024-12-13